A Study on Socio-Economic Factors Affecting Utilization of Maternal Health Care Services in Urban Community (Journal of Basic and Applied Research in Biomedicine, 2022)
Background: Even though the MMR dropped from 212 deaths per 100,000 live births in 2007-09 to 178 in 2010-12, India is behind the target of 103 deaths per live births to be achieved by 2015 under the United Nations-mandated Millennium Development Goals (MDGs).As per WHO, Three crucial factors understanding maternal deaths. Firstly lack of access and utilization of essential obstetric care. Secondly low social status of women in developing countries. Thirdly too much physical work together with poor diet also contributes to poor maternal outcomes. Out of these three factors, access and utilization of health care is the most crucial factor which is capable of reducing maternal morbidity and mortality. The present study was carried out to evaluate socio demographic correlates and barriers of maternal health care utilization in the urban community.    Objective:   To know the factors influencing the utilization of maternal health care services. METERIAL &METHODS; Study design: Cross sectional study. Area of study:   UHTC Kalal galli. Bijapur   (Urban field practice area)Participants: All married woman in the age group of 15-45 years who were either pregnant at the time of interview or delivered within last one year were included in the study.  Study period: January to March 2015Sample size: 134 mother Methods: Interview technique using pre tested   Proforma.   Statistical analysis: Percentage and chi-square test. Result: Utilization of maternal health services was found more among literate (70%) mothers compared to illiterate mothers. Utilization of maternal health services increased with increase in economic status. Major reasons for non-utilization of maternal service were not having a delivery complication in the past. (57%) Conclusion: The result reveals that educational level of women, exposure to mass media, birth order and wealth index are significant predictors in explaining the use of maternal health care services. There is a need of motivation and enhancing IEC activities for bringing desirable changes in the health care practice of the mother.